Overview of chemometrics in forensic toxicology - Sukhwinder Singh; Hanan Shakeel; Rakesh Sharma (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background The beginning of chemometrics within pattern recognition of the 1960s and 1970s is defined. This article shows a comprehensive deliberation on application of the chemometric techniques to chemical data analysis. Main body of the abstract Many review papers along with the usage of chemometrics in forensic chemistry have been available. The present article has been distributed into several parts which comprise chemometrics, its history, its function and chemometrics methods. Conclusion It is advised that these new chemometrics methods should be applied in forensic chemistry to get accurate and fast results.